Impact of mesoscale meteorological processes on anomalous radar propagation conditions over the northern Adriatic area - Telišman Prtenjak, Maja; Horvat, Igor; Tomažić, Igor; Kvakić, Marko; Viher, Mladen; Grisogono, Branko (Wiley, 2015)
The impact of mesoscale structures on the occurrence of anomalous propagation (AP) conditions for radio waves, including ducts, superrefractive, and subrefractive conditions, was studied. The chosen meteorological situations are the bora wind and the sporadic sea/land breeze (SB/LB) during three selected cases over a large portion of the northern Adriatic. For this purpose, we used available radio soundings and numerical mesoscale model simulations (of real cases and their sensitivity tests) at a horizontal resolution of 1.5 km and 81 vertical levels. The model simulated the occurrences of AP conditions satisfactorily, although their intensities and frequency were underestimated at times. Certain difficulties appeared in reproducing the vertical profile of the modified refractive index, which is mainly dependent on the accuracy of the modeled humidity. The spatial distributions of summer AP conditions reveal that the surface layer above the sea (roughly between 30 and 100 m asl) is often covered by superrefractive conditions and ducts. The SB is highly associated with the formations of AP conditions: (i) in the first 100 m asl, where trapping and superrefractive conditions form because of the advection of cold and moist air, and (ii) inside the transition layer between the SB body and the elevated return flow in the form of subrefractive conditions. When deep convection occurs, all three types of AP conditions are caused by the downdraft beneath the cumulonimbus cloud base in its mature phase that creates smaller but marked pools of cold and dry air. The bora wind usually creates a pattern of AP conditions associated with the hydraulic jump and influences distribution of AP conditions over the sea surface.